Adsorption, in vitro digestion and human gut microbiota regulation characteristics of three Poria cocos polysaccharides - Fangming Zhang; Hui Zheng; Tao Zheng; Pan Xu; Yao Xu; Yuxin Cao; Fan Jia; Yiqiong Zeng; Yubing Fan; Kai He; Xinwen Dai; Fengfei Hou; et al. (Food Science and Human Wellness)
Poria cocos (PC) is a famous traditional Chinese medicine (TCM) and a widely used healthcare ingredient, which has antiobesity, enhancing immunity and improving sleep effects. Traditionally, only water-soluble poria polysaccharide (WSP) is extracted and applied for clinical application, while insoluble polysaccharide (alkali-soluble poria polysaccharide, ASP) is discarded as herb residue. However, the whole PC has also been historically utilized as functional herbal food. Considering the beneficial role of dietary fiber and the traditional use of PC, ASP may also contribute substantially to the therapy function of PC. Compared to WSP, little attention has been paid to ASP and ASP modified product carboxymethyl poria polysaccharide (CMP) which has been used as an antitumor adjuvant drug. In this study, the oil, cholesterol, metal ions and polyphenols adsorption ability, in vitro simulated digestive and the gut microbiota fermentation characteristics of WSP, ASP and CMP were studied to evaluate the functional values of three P. cocos polysaccharides (PCPs). The results showed that all three PCPs had good adsorption capacity on cholesterol, polyphenols and metal ions (Cd2+/Zn2+/Mg2+), among which ASP showed the highest capacity than WSP and CMP. The adsorption capacity of all three PCPs on heavy metal ions (Cd2+/Zn2+) was stronger than that of non-heavy metal ions (Mg2+); The in vitro digestibility of all three PCPs was very low, but WSP was slightly higher than ASP and CMP; Moreover, the indigestible residue of all three PCPs could improve the richness and diversity of gut microbiota, among which ASP had the greatest influence. In general, ASP and CMP could significantly promote the proliferation of some probiotics and inhibit the growth of some harmful bacteria. The gut microbiota diversity of CMP was reduced, but the richness of probiotics, especially Parabacteroides distasonis was significantly enhanced compared with the ASP group, and the growth of harmful bacteria Klebsiella pneumoniae was inhibited after CMP treatment. The short-chain fatty acids (SCFAs) analysis results showed that all three PCPs could significantly promote the production of acetic acid, propionic acid and the total acid content compared with blank control group, and SCFAs producing activity was positively correlated with the proliferative capacity of probiotics. Taken together, the good adsorption characteristics and gut microbiota regulatory activity of ASP may lay foundation for its lipid-lowering and immune-improving function. Additionally, the probiotic effect of CMP and ASP indicated that except for only use the water extract of PC in clinic, CMP and ASP also can be used in healthcare to take full advantage of this valuable medicine.